Impact of vascular function on maximum power output in elite handball athletes - Bauer, P.; Kraushaar, L.; Most, A.; Hölscher, S.; Tajmiri-Gondai, S.; Dörr, O.; Troidl, C.; Bauer, T.; Nef, H.; Hamm, C.; Keller, T. (Research Quarterly for Exercise and Sport, 2019)
Purpose: To evaluate vascular function and its relationship to cardiorespiratory fitness in professional handball athletes. Method: We examined 30 male professional handball athletes (age 27 ± 4 y) and 10 male sedentary controls (age 26 ± 5 y) at rest. The workup included exercise testing via ergometry. To assess vascular function, a validated electronic model of the arterial tree (vasc assist 2®) was used. It replicates noninvasively acquired pulse pressure waves by modulating the relevant functional parameters of compliance, resistance, inertia, pressure, and flow. The maximum oxygen uptake (VO2max) was estimated using the validated heart rate ratio method. Results: Athletes had a significantly lower systolic and diastolic central blood pressure (cBP) compared to controls (102 ± 9/60 ± 9 vs. 110 ± 8/74 ± 9 mmHg, p < .01), whereas aortic pulse wave velocity (PWV) (6.2 ± 0.8 vs. 6.3 ± 0.5 m/s, p = .45) and augmentation index at a heart rate of 75 (Aix@75) (-4 ± 12 vs. -13 ± 16%, p = .06) were not different. Resistance index (R) (15.9 ± 4.4 vs. 10.6 ± 0.6, p = .001) and maximum power output (MPO) (3.55 ± 0.54 vs. 2.46 ± 0.55 Watt/kg, p < .001) were significantly higher in athletes compared to controls. We found no relevant correlation between MPO, resting heart rate, PWV, Aix@75, and cBP. A higher VO2max (p = .02) and a lower R (p < .01) were significant predictors of a higher MPO in athletes. Conclusion: R had an independent and strong correlation to MPO in athletes, which might help to disentangle the contribution of aerobic capacity and arterial function to physical power.